Introductory economics textbooks: what do they teach about sustainability? (2012)
In response to accelerating ecological deterioration, many universities have made commitments to integrate sustainability across the curriculum and to ensure they graduate ecologically responsible citizens. This study involves a content analysis of the coverage of environment-economy linkages in introductory economics textbooks. In North America, introductory economics courses tend to cover similar content and to rely heavily on textbooks. A small number of standard textbooks dominate this market. Standard introductory economics textbooks in current use in British Columbia, Canada were included in the study as well as three leading US textbooks. These were contrasted against a pair of micro/macro introductory texts explicitly written to address sustainability. The standard textbooks are found to largely ignore or mischaracterise environment-economy linkages and to include little content that would help further student understanding of sustainability. Universities that have made a commitment to integrate sustainability across the curriculum should examine carefully the textbooks used in their introductory economic courses and give preference to textbooks that have integrated sustainability-relevant content throughout the text and have addressed both environment-economy linkages and the challenge of sustainability with sophistication.